Analisis Konsep Keterampilan Dasar Layanan Konseling Dalam The Art of Helping karya Robert Carkhuff - Laela, Faizah Noer; Abidati, Athifa Azkial; Ariesta, Devi; Rahmayani, Devina; Azzahrah, Fitri Novalia (Jurusan Bimbingan dan Konseling Islam, 2023)
Basic skills in counseling services are an important foundation that supports an effective and meaningful counseling process. These skills are at the core of interactions between counselors and counselees, helping individuals overcome personal problems, understand themselves, and transform into more positive individuals. Robert R. Carkhuff, a leading figure in the field of counseling, discusses the concept of these basic skills in his book